-
If x = 3 + 2√2 , then the value of x6 + x4 + x2 + 1 is equal to x3
-
- 216
- 192
- 198
- 204
- 216
Correct Option: D
Expression = | ||
x3 |
Expression = | + | + | + | |||||
x3 | x3 | x3 | x3 |
Expression = x3 + x + | + | ||
x | x3 |
Expression = | ![]() | x3 + | ![]() | + | ![]() | x + | ![]() | |||
x3 | x |
Expression = | ![]() | x + | ![]() | 3 | - 3 | ![]() | x + | ![]() | + | ![]() | x + | ![]() | ||||
x | x | x |
Expression = | ![]() | x + | ![]() | 3 | - 2 | ![]() | x + | ![]() | ---(i) | ||
x | x |
Now, x = 3 + 2√2
∴ | = | ||
x | 3 + 2√2 |
= | × | ||
3 + 2√2 | 3 - 2√2 |
= | |||
x | 9 - 8 |
∴ x + | = 3 + 2√2 + 3 - 2√2 = 6 | |
x |
∴ Expression = (6)3 - 2 × 6 = 216 –12 = 204